AYURVEDIC RASAUSADHIES USED IN THE MANAGEMENT OF PRAMEHA W.S.R. TO DIABETES MELLITUS (AYUSHDHARA, 2020)
Diabetes Mellitus (DM) is a group of metabolic disorders characterised by hyperglycaemia due to absolute or relative deficiency of insulin. It is characterised by polyuria, polydipsia, polyphagia, rapid weight loss, fatigue etc. Based on similarities in signs and symptoms DM can be correlated with Prameha/Madhumeha in Ayurveda. Rasausadhies (metallic formulations) have been used in the treatment of Diabetes mellitus with its excellence for centuries but their scientific evaluation has not systematically established with modern tools. Rasausadhies have been popularly used since the period of great alchemist Nagarjuna, i.e. 8th century AD. In this time, invention of special processing techniques as Sodhana (purification), Marana (incineration), Sanskara (which increases the potency), Murchhana (triturating up to fine disintrigation) etc, have been established which are being used to convert the minerals and metals into easily consumable form and immediate showing the desirable effect. The present study deals with review of Rasausadhies from all the classics of Ayurveda which are mentioned in the treatment of Prameha.